2018
DOI: 10.9770/jesi.2018.5.3(17)
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between admission grades and academic achievement

Abstract: The predictive validity of standardized eligibility test for college admissions is a matter of debate and controversy. Standardized admission test came into vogue in the later part of the previous century. It gained traction due to various reasons. The main reason for this is the heterogeneity of high school GPA and the inherent drawbacks of teacher made tests. Often teacher-made tests fail to follow the basic rules of test construction, and are hence considered to be of poor quality. Standardized admission te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 26 publications
(46 reference statements)
1
24
0
2
Order By: Relevance
“…However, evidence has shown inconclusive results about their benefits since these admission tests are conditioned to students' sociodemographic characteristics (Mahlangu, 2020;Niessen et al, 2018;Zwick, 2012). Furthermore, Aitken (1982), Alnahdi (2015), Evans (2013), and Sulphey et al (2018) demonstrated that students' performance in higher education is closely linked to their academic performance in secondary education; thus, it is essential to complement higher education admission systems in such a way as to encourage the entry of talented students and increase access for traditionally underrepresented groups (Jia & Ericson, 2017;Koljatic & Silva, 2013, Santelices et al, 2019.…”
Section: Introductionmentioning
confidence: 99%
“…However, evidence has shown inconclusive results about their benefits since these admission tests are conditioned to students' sociodemographic characteristics (Mahlangu, 2020;Niessen et al, 2018;Zwick, 2012). Furthermore, Aitken (1982), Alnahdi (2015), Evans (2013), and Sulphey et al (2018) demonstrated that students' performance in higher education is closely linked to their academic performance in secondary education; thus, it is essential to complement higher education admission systems in such a way as to encourage the entry of talented students and increase access for traditionally underrepresented groups (Jia & Ericson, 2017;Koljatic & Silva, 2013, Santelices et al, 2019.…”
Section: Introductionmentioning
confidence: 99%
“…The result of the study indicated that the CGPA at the end of the pre-university examination predicts educational performance of the new entrants. Also, [25] conducted a study to establish if there is a link between new entrants' admission scores (high school GPA and GAT) and their educational performance. The study was carried out in a Saudi Arabian University with a sample size of 1,368 business students undergoing undergraduate study.…”
Section: Conceptual and Empirical Review 21 Student Intakementioning
confidence: 99%
“…The quality of higher education in general, and that of accounting education in particular has been a major issue of debate worldwide (Awayiga et al, 2010;Sulphey, 2017;Sulphey & Al Kahtani, 2018;Zureigat, 2015). There are many who opine that the present educational model for accounting has failed in the area of employability skill development.…”
Section: Review Of Literaturementioning
confidence: 99%